"It's Somebody Else's Milk": Unraveling the Tension in Mothers of Preterm Infants Who Provide Consent for Pasteurized Donor Human Milk. (February 2016) - Esquerra-Zwiers, Anita; Rossman, Beverly; Meier, Paula; Engstrom, Janet; Janes, Judy; Patel, Aloka
Background: Pasteurized donor human milk (DHM), rather than preterm infant formula, is recommended for premature infants when mother's milk is not available. Objective: This study explored the maternal decision-making process in providing consent for DHM feedings. Methods: In-depth semistructured interviews were conducted with 20 mothers of premature (mean gestational age = 27 weeks, birth weight = 942 grams) infants hospitalized in the neonatal intensive care unit (NICU) in this qualitative, descriptive study. Conventional content analysis was used to analyze the data. Results: Although only 1 mother had any previous knowledge of DHM, all mothers provided consent for DHM because they "wanted what is best for my baby." Mothers trusted that DHM was better than formula when their infant's feeding requirements exceeded their own milk supply. However, most mothers described a tension between wanting their infants to receive only "their" milk and DHM being "somebody else's milk." This desire to be the only provider of human milk was more common than concerns about the quality and safety of DHM. The mothers' tension was mediated by trusting the NICU clinicians' recommendations, having adequate time to make an informed decision, observing the positive outcomes of DHM, and feeling empowered that they made the best decision for their infant. Conclusion: The experiences of these mothers reflect the importance of approaching mothers for consent only when DHM is needed, respecting mothers' beliefs and values about DHM, and providing help in mediating any tension with regard to their infants receiving "somebody else's milk."